2020
DOI: 10.1016/j.jsat.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Findings from the recovery initiation and management after overdose (RIMO) pilot study experiment

Abstract: This pilot study evaluated the feasibility of the Recovery Initiation and Management after Overdose (RIMO) intervention to link individuals to medication-assisted treatment (MAT) following an opioid overdose. The study team worked with the Chicago Fire Department to train Emergency Medical Service (EMS) teams to request permission from individuals after an opioid overdose reversal to release their contact information; individuals were subsequently contacted by the study team for participation. A mixed-methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 56 publications
(47 reference statements)
0
36
0
Order By: Relevance
“…Pilot studies of peer recovery coaching interventions in hospital emergency departments targeting people who have experienced an opioid overdose have been performed. One study ( n =75) demonstrated a much greater likelihood of linkage to programs that provide MOUD (20x more likely) and longer retention in MOUD treatment among people who overdosed and received peer recovery coaching as compared to those who overdosed and received a passive referral to community substance abuse treatment programs [ 109 ]. A study of 1329 emergency department peer coaching contacts in Rhode Island demonstrated high rates of patients receiving naloxone training by peer recovery coaches (88.7%) and agreeing to continue contact with a peer recovery coach (86.8%) [ 110 •].…”
Section: Opportunities For Interventionmentioning
confidence: 99%
“…Pilot studies of peer recovery coaching interventions in hospital emergency departments targeting people who have experienced an opioid overdose have been performed. One study ( n =75) demonstrated a much greater likelihood of linkage to programs that provide MOUD (20x more likely) and longer retention in MOUD treatment among people who overdosed and received peer recovery coaching as compared to those who overdosed and received a passive referral to community substance abuse treatment programs [ 109 ]. A study of 1329 emergency department peer coaching contacts in Rhode Island demonstrated high rates of patients receiving naloxone training by peer recovery coaches (88.7%) and agreeing to continue contact with a peer recovery coach (86.8%) [ 110 •].…”
Section: Opportunities For Interventionmentioning
confidence: 99%
“…Effective treatment (stage 2) includes rapid access to medication-based treatment and other psychosocial services ( 134 ). Providing a community-based recovery coach or case manager can improve the transfer rate from crisis to medication-based treatment ( 135 , 136 ). Stepped care procedures, such as the hub and spoke or collaborative care models (stage 3), are used to modify a person's OUD medications, medical care and psychosocial needs over 6 or more months, using the same approach that primary care practices (PCPs) apply to chronic diseases.…”
Section: Lifestyle Medicine Domain-specific Findings and Recommendatimentioning
confidence: 99%
“…The program is also staffed with a DATA‐waivered nurse practitioner who provides buprenorphine, a licensed chemical dependency counselor who provides substance abuse counseling, and peer recovery coaches who provide support groups and regular check‐ins on participants of the program, and preliminary results suggest that 88% of people are retained in treatment at 30 days 45,46 . Programs such as EPICC (Engaging Patients in Care Coordination) in St. Louis, the RIMO (Recovery Initiation and Management After Overdose) intervention in Chicago, Project POINT (Planned Outreach, Intervention, Naloxone, and Treatment) in Indiana, and AnchorED (Anchor Recovery Center and Emergency Department) in Rhode Island also leverage the lived experience of peer recovery coaches within their programs, because coaches relate to the common challenges and barriers to sustaining treatment 47–50 …”
Section: Resultsmentioning
confidence: 99%